Keberlanjutan Rumah Susun Sederhana Milik (Rusunami) : Solusi Hunian Layak bagi Masyarakat Berpenghasilan Rendah di Surabaya - Mas’odi Mas’odi; Ika Devy Pramudiana; Sri Roekminiati; Nihayatus Sholichah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
This study aims to explore the sustainability of Rumah Susun Sederhana Milik (Rusunami) as a viable housing solution for Low-Income Communities (MBR) in Surabaya. The study adopts a qualitative approach using a case study method. Data were collected through in-depth interviews with residents, management representatives, and local government officials, as well as through field observations. Data analysis was conducted based on the indicators of the Adequate Housing Framework by UN-Habitat, which include secure tenure, affordability, habitability, accessibility, location, and the availability of basic services. The findings reveal that Rusunami is capable of providing affordable housing for MBR with a permanent ownership system, despite facing major challenges such as administrative barriers and low financial literacy. The program has proven to contribute to improving the quality of life of residents and reducing socio-economic inequalities. To ensure long-term sustainability, strategic measures are needed, such as simplifying administrative procedures and enhancing the financial literacy of the community. Development recommendations include improving the administrative system to ensure the program can be accessed by a larger number of MBR optimally.